2009
DOI: 10.1007/bf03405272
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Acceptance of Self-sampling for Human Papillomavirus across Ethnolinguistic Groups of Women

Abstract: Objectives: Immigrant and low socio-economic (SES) women in North America underutilize Papanicolaou screening. Vaginal swab self-sampling for oncogenic human papillomavirus (HPV) has the potential to increase cervical cancer screening participation. The purpose of this qualitative study was to understand the perceptions of lower SES and immigrant women regarding self-sampling for HPV.Methods: Eleven focus-group interviews were conducted: one with Canadian-born English-speaking lower SES women, and two groups e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 17 publications
2
70
1
Order By: Relevance
“…A pair of studies, 22,23 one 23 done among women at high risk for cervical cancer and the other done within a large Mexican population, 22 reported self-sampling to be preferable over clinician testing due to less embarrassment and being more comfortable with the test. Contrary to most studies 16,18,2830 that have shown that women preferred clinician-collected samples over self-sampling, we found that among participants who stated a preference for either test, self-sampling was more preferable. We did not find differences between tests in participants’ perception of test accuracy or participants’ perception that the test is performed correctly.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A pair of studies, 22,23 one 23 done among women at high risk for cervical cancer and the other done within a large Mexican population, 22 reported self-sampling to be preferable over clinician testing due to less embarrassment and being more comfortable with the test. Contrary to most studies 16,18,2830 that have shown that women preferred clinician-collected samples over self-sampling, we found that among participants who stated a preference for either test, self-sampling was more preferable. We did not find differences between tests in participants’ perception of test accuracy or participants’ perception that the test is performed correctly.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not find differences between tests in participants’ perception of test accuracy or participants’ perception that the test is performed correctly. Concerns about the accuracy of the test, 29 uncertainty over performing the test correctly 18,31 and fear of harm 18 had been the most commonly cited factors for participants not preferring self-sampling over cervical cytology testing in other settings. The difference between our finding and those of others may be due to providing education in which concerns were addressed before having participants collect their own cervico- vaginal samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the data collected via baseline and follow-up interviews were primarily based on self-report. Previous studies have noted that women tend to overstate their participation in cervical cancer screenings [43]. There is also the possibility for selection bias as study participants were already seeking services at a healthcare clinic and may be more proactive in accepting cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Anhang et al [19] observed among an urban population in New York City that, despite describing the self-HPV as easy to be used (67%) and not painful (67%), most of the women (68%) still preferred the physician sampling mainly because ''the doctor knew how to do the test correctly.'' Studies on women immigrated to Canada, the United Kingdom, or the United States reported 2 significant barriers to self-HPV, the women's concerns that they would not take the sample properly and their fear of experiencing pain [20,22,23]. Another Canadian study, performed on women from a primary care population, aged 15 to 49 years and accustomed to a routine physical examination and Pap smear, reported also that a significant proportion of women (54%) preferred physician sampling.…”
Section: Discussionmentioning
confidence: 99%